LARYNGEAL MASK AIRWAY INSERTION: COMPARISON OF SEVOFLURANE WITH PROPOFOL IN ADULTS - KUMAR, VIVEK; SETLUR, RANGARAJ; GHODKE, SANDHYA; JAHAN, NIKHAT; HIREMATH, RAVISHEKAR N (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Methods: A cross-sectional observational study was conducted on patients scheduled for vascular, reconstructive, gynaecological, and day care surgeries for whom propofol (P) and sevoflurane (S) were used as induction agent for LMA insertion. All patients who fulfilled the inclusion and exclusion criteria and had given propofol or sevoflurane at various departments during the specified duration were included in the study and data were collected using pre-defined protocol. A total of 100 consecutive patients (50 patients in each group) were included in the study. Objectives: The objectives of the study were to evaluate and compare sevoflurane in one vital capacity breath with propofol in dose of 2 mg/kg for ease of laryngeal mask airway (LMA) insertion in adults. Results: The mean age for sevoflurane (S) group and propofol (P) group was 35.30, standard deviation (SD) 8.74 and 34.88, SD 9.37, respectively. Heart rate (HR) at 2 min, 3 min, and 4 min after induction showed a fall with propofol which was statistically significant. There was statistically significant difference in systolic blood pressure at on 1 min, 2 min, 3 min, and 4 min when compared between the two groups. A statistically significant fall in the systolic blood pressure in Group P was noted when compared to Group S. There was statistically significant difference in diastolic blood pressure at 4 min when compared between the two groups. A fall in the diastolic blood pressure in Group P was noted when compared to Group S at 4 min. There was fall in blood pressure in Group P when compared with Group S and this was significant. Fall in oxygen saturation in 3 and 4 min was significant. However, this fall was not clinically significant, as the values remained above 94%. There was increase in end-tidal carbon dioxide in 1, 2, 3, and 4 min and was statistically significant between the two groups. Sevoflurane took longer time for induction and LMA insertion. Loss of eye lash reflex, jaw relaxation, and LMA insertion were lost earlier with propofol and were statistically significant. The overall LMA insertion was excellent with propofol in 50 patients and with sevoflurane 48 patients had excellent condition and two were satisfactory. Conclusion: In our study, sevoflurane was associated with good hemodynamic stability, but quality of anesthesia provided with propofol was superior. Delayed jaw relaxation with sevoflurane when compared to propofol delayed LMA insertion. The overall insertion was excellent with propofol with all 50 patients as compared to sevoflurane.